Teachers’ Voice toward the Use of Storyboard in Teaching Writing Narrative Text - Shilvi Alfu Rohmatin; Zainul Aminin (Universitas Nusantara PGRI Kediri, 2024)
Writing is an essential skill for students to master. It is essential for communication, academic success, and future careers. However, many students struggle with writing due to variety of challenges. To address this, teachers can use engaging media like storyboards. Storyboards combine visual and textual elements, helping students plan and organize their narratives more effectively. The objective of this research is to explore the use of storyboards in teaching writing narrative text and the benefits and challenges of storyboarding in writing. The research design of this research was basic interpretative qualitative research. This research was conducted on seven English teachers in Surabaya and Gresik who met the predetermined criteria. To gather data, the researchers employed open-ended questionnaires and semi-structured interviews. The findings indicate that teachers use this medium to create fun learning. Teachers used different types of storyboards, including paper and digital ones. The results showed that storyboards significantly enhanced students' engagement and understanding of narrative text. However, this media also has challenges teachers and students may face. Overall, this research provides valuable insights into how teachers perceive and utilize storyboards for teaching narrative writing. The results of the research are expected to be a reference and provide data relevant to the views and experiences of teachers.